Gereja dan Layanan Kesehatan Holistik untuk Lansia: Studi di Jemaat GKE Eppata dan GKE Eben Ezer Banjarmasin - Keloso; Lia afriliani; Rena Berkatni (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2025)
This study aims to describe the role of the church in supporting health services for the elderly, focusing on GKE Eppata and GKE Eben Ezer in Banjarmasin. Through a qualitative approach, data was collected through interviews, observations, and literature reviews. The results showed that both congregations have an active Elderly Ministry Section, with various programs such as elderly worship, healthy gymnastics, and diakonia visits. At the GKE Eppata, physical health services are conducted regularly in collaboration with external parties, while at the GKE Eben Ezer, physical health services have not yet resumed post-pandemic. These services reflect the holistic health approach the physical, mental, social, and spiritual aspects. In addition, the role of the church also supports the achievement of successful aging through elderly awareness of personal health and active involvement in congregational life. The elderly are the image of God and part of the Body of Christ, so the church is responsible for caring for them. This research recommends strengthening holistic services and developing strategies to reach out to the elderly who are not yet involved in church services.